1999
DOI: 10.1016/s0002-9440(10)65232-7
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial L-Selectin Ligands Are Likely to Recruit Lymphocytes into Rejecting Human Heart Transplants

Abstract: L-selectin-dependent lymphocyte extravasation is a hallmark of acute heart allograft rejection in rats. On screening over 600 endomyocardial biopsies (EMBs), taken at different time points after heart transplantation in man , we identified 91 samples with histological signs of acute rejection. Rejection and nonrejection EMBs were analyzed for the presence of properly glycosylated , ie , sulfated sialyl Lewis-x (sLex) decorated L-selectin ligands. Two anti-sLex (2F3 and HECA-452) and one anti-6-or 6 -sulfated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 39 publications
(37 reference statements)
8
55
0
3
Order By: Relevance
“…Once chronic inflammation occurs, these vessels, which bind L-selectin⅐IgM chimeric protein in a Ca 2ϩ -dependent manner, appear. Our observations of de novo for- mation of HEV-like vessels are similar to those described previously in various human chronic inflammatory diseases, such as rheumatoid arthritis, lymphocytic thyroiditis, inflammatory bowel diseases, and in acute heart allograft rejection (14)(15)(16)(17)34). However, none of the previous studies showed disappearance of HEV-like vessels by removing causes that led to their formation.…”
Section: Discussionsupporting
confidence: 90%
“…Once chronic inflammation occurs, these vessels, which bind L-selectin⅐IgM chimeric protein in a Ca 2ϩ -dependent manner, appear. Our observations of de novo for- mation of HEV-like vessels are similar to those described previously in various human chronic inflammatory diseases, such as rheumatoid arthritis, lymphocytic thyroiditis, inflammatory bowel diseases, and in acute heart allograft rejection (14)(15)(16)(17)34). However, none of the previous studies showed disappearance of HEV-like vessels by removing causes that led to their formation.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, previous studies show that anti-CD62L mAbs or CD62L deficiency are not generally immunosuppressive, but result in altered leukocyte distribution and kinetics of immune responses (20 -23). As shown in this study and previously (19,39), anti-CD62L mAbs do not prolong allograft survival, and CD62L Ϫ/Ϫ recipients are fully capable of vigorously rejecting allografts. Instead, interfering with CD62L function inhibits tolerization, and this is not due to costimulatory influences (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Tumor HEVs are structurally and phenotypically similar to HEVs from patients suffering from autoimmune or chronic inflammatory diseases such as rheumatoid arthritis, inflammatory bowel diseases, and autoimmune thyroiditis (15,18,19). The presence of HEVs in these pathologies has been shown to participate in the development and the maintenance of chronic inflammation through the recruitment of large numbers of lymphocytes (27,28). In contrast, HEVs have never been observed in normal nonlymphoid tissues.…”
Section: Discussionmentioning
confidence: 99%